Advantages of using information and communications in psychodiagnostics over traditional methods. - Mamajonova Shakhzoda (Genius Journals, 2023)
The article provides information about the developing modern computer software and its capabilities. Also, the advantages, nature and methods of using modern information and communications in the field of psychodiagnostics over traditional methods are widely covered
Keywords: psychology; psychodiagnostics; psychometrics; criteria